ANALISIS POSITIONING SMARTFREN DENGAN PERCEPTUAL MAPPING KONSUMEN DALAM PERSAINGAN PASAR MOBILE INTERNET PROVIDER DI SURABAYA - Nandya Whita Moniva; Sri Hartini (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
This paper intends to analyze Smartfren's position in the competition of Mobile Internet Providers in Surabaya by using Multidimensional Scaling. With Perceptual Map, Smartfren can evaluate marketing strategies that are being carried out by looking at the position of competitors. The study looked at 125 respondents from various circles who knew five brands of Mobile Internet Providers in Surabaya. The results showed that Smartfren had its own differentiation so Smartfren needed to develop a marketing strategy through 5P's (Product, Price, Place, Promotion).Keyword: Multidimensional Scalling, Perceptual Map, Marketing Strategy, Mobile Internet Provider